PESAN ALQURAN DALAM KERJASAMA MUSA DENGAN SYU‘AYB TENTANG PENGELOLAAN BISNIS - Alimin Mesra (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2016)
Prophet Moses and Prophet Syu'ayb companion ultimately led them to work together. This case reveals a number of values that should be developed and applied in life related to business management. This story (Q.s. al-Qashash [28]: 23-28) reveals a relation between employyees and owners of capital, recruitment patterns, appreciation of performance, professionalism, and some related matters. The cooperation between them can be considered as a symbolic learning delivered by the Quran, especially in business development. This story also shows that a partnership should be based on a clear contract that shows such related materials, working period, the amount of wages, security, and others related to their right and obligation. DOI: 10.15408/aiq.v4i1.2530